Durability of resistant lines of brinjal (Solanum) for resistance against bacterial with (Ralstonia Solanacearum) under sub-humid condition of Jharkhand* - SHARMA, J P; KUMAR, S (The Indian Journal of Agricultural Sciences, 2011)
A study was undertaken during 1994-2004 to evaluate the durability of designated resistant test entries of All India Go-coordinated Vegetable Improvement Research Programme. A total of 22 resistant and 3 other promising entries of HARP, Ranchi were tested for 8, 6, 4 and 3 years in post-monsoon seasons of in bacterial sick plot (3.84 to 9.14 x 1 O5 cfidg soil of predominant presence of biovar V of race 1). The entries, viz 'CH 249' ('Swarna Shyamli'), 'CH 309' ('Swarna Pratibha'), 'BB 64', 'JC 8', 'Arka Keshav" and 'Arka Nidhi' showed stability in resistance to bacterial with. Whereas 'BB 60 C' and 'SM 6-6' showed instabilility in resistance to bacterial wilt, whereas 'Swama Shree', 'JC l'and 'SM 141' showed stable and moderately resistant to bacterial wilt in sub-humid condition of Jharkhand. These variations were presumably due to genotype x environment interaction of Ralstonia solanacearum sub-humid condition of Jharkhand.